2022
DOI: 10.21037/jtd-22-372
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of pulmonary nodular mucinous adenocarcinoma and tuberculoma with dynamic CT: a retrospective study

Abstract: Background: Pulmonary nodular mucinous adenocarcinoma (PNMA) tends to be easily misdiagnosed as tuberculoma in practice. In this study, we aimed to discriminate PNMA from tuberculoma with dynamic computed tomography (CT).Methods: In this study, 38 consecutive pathologically confirmed cases of PNMA and 23 cases of tuberculoma from January 2015 to December 2019 were retrospectively collected. The mean CT attenuations of each lesion were examined. The values on the plain scan, the venous scan, and the enhanced va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the diagnosis of lung cancer and tuberculosis, CT scans, especially the CT dynamic contrast-enhanced scan is an important method. There were many reports on CT for lung adenocarcinoma and pulmonary tuberculoma, but there were few reports about the CT features of PNMA and PTB [13,27,28]. As a result of this study, we determined that the mean CT value of PTB on plain scan was 31.00HU and the CT value of PNMA was 17.00HU, whereas ΔCTV was 25.49HU in the PNMA group and 4HU in the PTB group.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the diagnosis of lung cancer and tuberculosis, CT scans, especially the CT dynamic contrast-enhanced scan is an important method. There were many reports on CT for lung adenocarcinoma and pulmonary tuberculoma, but there were few reports about the CT features of PNMA and PTB [13,27,28]. As a result of this study, we determined that the mean CT value of PTB on plain scan was 31.00HU and the CT value of PNMA was 17.00HU, whereas ΔCTV was 25.49HU in the PNMA group and 4HU in the PTB group.…”
Section: Discussionmentioning
confidence: 75%
“…Computed tomography (CT) is widely used for tumor detection, staging and therapeutic response monitoring in clinical practice [12]. There have been few studies concerning the differential diagnosis of PNMA and PTB [13], results revealed that satellite lesions, were more often observed in the PTB group and the mean CT attenuation of PTB shown on the plain scan was signi cantly higher than that of PNMA (35.15 ± 16.00 vs. 24.00 ± 12.67 HU; P < 0.01). However, the enhanced value of PTB on venous scan was signi cantly lower than that of PNMA (13.44 ± 13.40 vs. 22.52 ± 14.00 HU; P = 0.02).…”
Section: Introductionmentioning
confidence: 99%
“…CT scanning, especially CT dynamic contrast-enhanced scanning, is a valuable tool in the diagnosis of lung cancer and tuberculosis. The CT features of lung adenocarcinoma and pulmonary tuberculoma have received much attention in the literature, but PNMA and PTB have received fewer reports [ 12 , 29 , 30 ]. As a result of this study, we determined that the mean CT value of PTB on plain scan was 31.00 HU and that the CT value of PNMA was 17.00 HU, whereas the ΔCTV was 25.49 HU in the PNMA group and 4 HU in the PTB group.…”
Section: Discussionmentioning
confidence: 99%
“…There may be overlap in the morphology and CT features between PNMA and PTB. In fact, many cases of PNMA are misdiagnosed as PTB in clinical practice, which leads to missing the best treatment time, leading to a shortened survival time [ 12 , 13 ]. Distinguishing PNMA and PTB before treatment in a timely manner is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation